UTILIZING EXAMPLES OF FOLK PEDAGOGY IN CHILD-REARING - Abdaliyeva, Peruza Isaevna (SCIENCE and SOCIETY, 2026)
The article deals with the problems of educating children by comprehensively developed people using samples of Karakalpak folk pedagogy in family education.
Keywords: family; folk values; customs; traditions; fairy tales; termes (verse-singing speech); riddles; proverbs; lullabies.